Influence of substrate surface energy and surfactant on crystalline morphology and surface defect density in hydrothermally-grown ZnO nanowires. (April 2018) - Park, Ji-Sub; Mahmud, Imtiaz; Shin, Young-Chul; Choi, Jun-Chan; Kim, Byeonggon; Shin, Han Jae; Choi, Yoonseuk; Kim, Hak-Rin
Abstract: We investigated the influence of substrate surface energy before seed layer formation on hydrothermally grown zinc oxide (ZnO) nanowires (NWs). The qualities of ZnO NWs prepared by the surface-enhanced growth method with ultraviolet ozone (UVO) treatment were analyzed in terms of crystalline morphology and surface defect density, and were compared with those of ZnO NWs prepared by the conventional bulk-enhanced growth method adopting polyethyleneimine (PEI) as the surfactant in an aqueous growth solution. In both cases, a positive effect on the morphological properties and crystallinity of ZnO NWs was observed; however, the surface-enhanced growth method was more efficient for obtaining hydrothermally grown ZnO NWs with higher aspect ratios and larger surface areas. The ZnO NW growth rate in the surface-enhanced growth method was two times faster than in the conventional bulk-enhanced growth method. Photoluminescence (PL) spectra and time-resolved PL (TR-PL) responses indicated that a high density of oxygen vacancies on ZnO NW surfaces was produced by the surface-enhanced growth method, because highly oriented ZnO NWs can be grown without surface passivation effect, on the contrary with the bulk-enhanced growth method. Graphical abstract: